Apoptosis and genome instability in children with autoimmune diseases. (27th November 2018) - Mihaljevic, Olgica; Zivancevic-Simonovic, Snezana; Milosevic-Djordjevic, Olivera; Djurdjevic, Predrag; Jovanovic, Danijela; Todorovic, Zeljko; Grujicic, Darko; Radovic-Jakovljevic, Marina; Tubic, Jovana; Markovic, Aleksandra; Paunovic, Milan; Stanojevic-Pirkovic, Marijana; et al.
Abstract: As apoptosis and genome instability in children with autoimmune diseases (AIDs) are insufficiently investigated, we aimed to analyse them in peripheral blood lymphocytes (PBLs) of children and adolescents with Hashimoto's thyroiditis (HT), Graves' disease (GD) and type 1 diabetes mellitus (T1DM), including possible factors that could affect their occurrence. The study population included 24 patients and 19 healthy controls. Apoptotic cells were detected using an Annexin V-FITC/7-AAD kit. Genome instability was measured as micronuclei (MNs) frequency using the cytokinesis-block MN assay. In addition, comet assay was performed for determination of genome instability as genome damage index (GDI) in new subpopulation of patients with T1DM. The percentage of apoptotic PBLs in patients with AID was significantly lower than in control subjects. There was a positive correlation between thyroid-stimulating homone (TSH) concentration and the proportion of cells in late stage apoptosis in patients with autoimmune thyroid diseases (AITDs). The MN frequency in patients was significantly higher than in controls. Individuals with HT or T1DM had a significantly higher MN frequency than those with GD. Similarly, the value of GDI in patients with T1DM was significantly higher than in controls. The level of apoptosis was positively correlated with MN frequency as well as with GDI in patients with AID. In conclusion, children with AITD (HT and GD) and T1DM have a significantly lower level of apoptosis in PBLs and significantly higher MN frequency as GDI than healthy subjects. Apoptosis and the level of genome instability in these patients with AID are positively correlated.